2003
DOI: 10.1042/bst0311125
|View full text |Cite
|
Sign up to set email alerts
|

Fatty acid recycling in adipocytes: a role for glyceroneogenesis and phosphoenolpyruvate carboxykinase

Abstract: FA (fatty acid) recycling in adipose tissue appears to be an important pathway for regulating FA release into the blood during fasting. Re-esterification requires G3P (glycerol 3-phosphate), which cannot be synthesized from glucose because glycolysis is much reduced under such circumstances. In addition, G3P can scarcely originate from glycerol since glycerol kinase has a very low activity in white adipose tissue. It was shown about 35 years ago that a metabolic pathway named glyceroneogenesis, which allows G3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
56
0
3

Year Published

2006
2006
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(59 citation statements)
references
References 2 publications
0
56
0
3
Order By: Relevance
“…11 These pathways tend to reduce the output of lipolytic products and favor local storage or metabolism of fatty acids, and therefore constitute a key divergence between the GC and PPARg pathways. The lack of reduction in PEPCK expression under HiCORT conditions was unexpected; 49,50 however, PEPCK expression is also modulated by the nutritional status, 51 and the present conditions may not have been optimal to reveal an effect of CORT thereupon.…”
Section: Pparc In Rats With Hypercorticosteronemia M Berthiaume Et Almentioning
confidence: 70%
“…11 These pathways tend to reduce the output of lipolytic products and favor local storage or metabolism of fatty acids, and therefore constitute a key divergence between the GC and PPARg pathways. The lack of reduction in PEPCK expression under HiCORT conditions was unexpected; 49,50 however, PEPCK expression is also modulated by the nutritional status, 51 and the present conditions may not have been optimal to reveal an effect of CORT thereupon.…”
Section: Pparc In Rats With Hypercorticosteronemia M Berthiaume Et Almentioning
confidence: 70%
“…Although most investigators probably agree that modulation of plasma free fatty acid flux (via esterification in white adipose tissue) offers therapeutic benefits, it is difficult to determine whether manipulation of glyceroneogenesis is solely responsible and/or whether altered glucose flux in adipose tissue plays a role. Namely, contrary to the seminal work of Hanson and colleagues (24), recent in vitro studies typically quantify pyruvate flux to triglyceride glycerol in the absence of glucose (10,12,25,26). We became intrigued by the notion that glyceroneogenesis could play an important, if not predominant, role in affecting triglyceride glycerol production in white adipose tissue in vivo (7, 9 -12); however, the experimental methods used in those studies deserve consideration because artifacts in the tracer techniques can affect the interpretation of the data (discussed below).…”
Section: Discussionmentioning
confidence: 90%
“…For example, although pyruvate was incorporated into triglyceride glycerol, the addition of glucose and insulin led to a ϳ5-fold reduction in the conversion of pyruvate to triglyceride glycerol, suggesting a dynamic control of triglyceride glycerol production (24). Since its discovery, the glyceroneogenic pathway was mostly overlooked; however, recent interest in the role of peroxisome proliferator-activated receptor-␥ agonists has demonstrated that glyceroneogenic flux is sensitive to pharmacological manipulation (10,12,25,26). Although most investigators probably agree that modulation of plasma free fatty acid flux (via esterification in white adipose tissue) offers therapeutic benefits, it is difficult to determine whether manipulation of glyceroneogenesis is solely responsible and/or whether altered glucose flux in adipose tissue plays a role.…”
Section: Discussionmentioning
confidence: 99%
“…The abundance of both NEFA and glucose facilitates esterification. In catabolic states glucose levels cannot support esterification; rather, phosphoenolpyruvate carboxykinase provides glycerol backbones from pyruvate via the glyceroneogenesis pathway (for review, see Forest et al (99) ). Accordingly, phosphoenolpyruvate carboxykinase expression and activity are increased with fasting (100) and b-AR agonist treatment (101) , both highly catabolic states.…”
Section: Lipolysis and Re-esterificationmentioning
confidence: 99%